Penanganan Kasus Cystitis Hemoragik pada Kucing Mix Persian di Klinik Hewan Awal Care - Ramadani, Amanda Haristia Ramadani; Mirjawal; Tiara Widyaputri; Mira Fatmawati; Andreas Bandang Hardian (Jurnal Veteriner dan Biomedis, 2025)
Hemorrhagic Cystitis is an inflammation accompanied by bleeding that occurs in the urinary bladder characterized by thickening of the urinary bladder wall and has clinical symptoms of hematuria or urine with blood, dysuria, abdominal distension and pain when palpated in the abdominal area. Patients with symptoms of weakness, loss of appetite and vomiting. An examination was carried out by a doctor and a pain response was found in the abdomen, after further observation by palpation, an enlarged VU was felt and hematuria was present. The results of the Ultrasonography examination found a thickening of the urinary bladder wall, then a microscopic examination of native urine found red blood cells. Hematology results showed an increase in parameters in leukocytes, and granulocytes and a decrease in platelets indicating acute infection and also bleeding or acute inflammation. A blood chemistry examination showed an increase in BUN and Creatinine levels caused by post-renal Azotemia. The results of the signaling and anamnesis were associated with the results of the supporting examination of the chika cat diagnosed with Hemorrhagic Cystitis and cystotomy treatment was performed. Treatment and handling are done after cystotomy surgery with treatment in the form of antibiotics as causative therapy, musculorelaxants and anti-fibrinolytics as symptomatic therapy, and multivitamins as supportive therapy. Handling is done by giving special diet feed, catheterization, and laser therapy on post-operative wounds.